Design, development and performance evaluation of green nipah banana (Musa acuminata x balbisiana colla ABB group) peeling tool for small scale industry - Zainal A'bidin, Farahana Nabilah (2021)
Peeling is one of the processes in the making of banana chips. In the current Malaysian industry, the peeling process is still done using the manual method, which uses hand and kitchen knife. The weakness of using manual peeling is that it requires knife-handling skills to prevent pulp from being damaged, time-consuming, and unsafe. Therefore, the study aims to develop a banana peeling tool that successfully removes the skin of green Nipah banana in a shorter time and with minimal pulp loss. In banana chips processing, bananas under certain conditions are essential as they will affect the texture for drying and frying. The fruit needs to be stiff and starchy; thus, certain properties during its ripening period need to be evaluated to examine the suitable ripening days to process the bananas. The study involves several properties evaluated, such as the physicochemical and mechanical, throughout its ripening days. Based on the result, the green Nipah banana's colour and mechanical properties were correlated with ripening days. The colour of the peel also gradually changes from dark green to lighter green and yellow tint. As for proximate analysis, only crude fibre and crude protein correlate with ripening days. Crude fibre increases by 52.69 % on the upper bunch and 52.12 % for the lower bunch from day 1 to day 5, while crude protein decreases by 61.11 % for the upper bunch and 93.55 % for the lower bunch from day 1 to 5. Total soluble solids (TSS) and fructose also correlate with ripening days. TSS increases throughout its ripening days when the fructose decreases. TSS on the upper bunch increases by 36.73 % on the upper bunch, while the lower bunch decreases to 41.67% on day 3 and increases back by 38.23 % to day 5. Firmness, adhesiveness, and penetration force decrease while compression force increases throughout its ripening days. Firmness decreases by 12.04 %, 21.25 %, and 9.18 % for top, middle and bottom finger positions respectively for upper bunch position. As for the lower bunch, firmness decreases by 11.15 %, 9.09 % and 20.60% for top, middle and bottom, respectively. Adhesiveness decreases by 26.72 %, 37.85 % and 36.26 % for top, middle and bottom finger positions respectively for upper bunch position. As for the lower bunch, adhesiveness decreases by 57.50 %, 64.68 % and 63.94 % for top, middle and bottom, respectively. Penetration force decreases by 13.15 %, 12.14 % and 27.92 % for top, middle and bottom finger positions respectively for upper bunch position. As for the lower bunch, penetration force decreases by 15.65 %, 14.61 % and 13.15 % for top, middle and bottom, respectively. Compression force increases by 64.06 %, 44.43 % and 60.75 % for top, middle and bottom finger positions respectively for upper bunch position. For the lower bunch, compression increases by 129.62 % and 46.22 % for top and middle finger position respectively while the bottom remains constant The development of the peeling tool started with design considerations from a morphology chart, and then several conceptual designs were generated. After that, a matrix decision was made to evaluate the best design and assembly parts for fabrication was discussed in this study. A peeling tool was designed and developed as an alternative to the current manual method. The final design was developed by improving the first design. The weakness of the first design is that the force needed for the peeling process is high and takes longer peeling time as the user needs to use one hand to hold the banana while the other hand to push between the skin and pulp of the banana for banana skin removal. Performance of the peeling tool was obtained from its peeling time, pulp loss, force and deformation analysis. The peeling tool is tested to increase the peeling rate by 60% with less than 1.9% peel loss. Minimal deformation was obtained from the Finite Element Method (FEM) analysis. Besides, the maximum force on the tool was smaller than the yield force of the material; thus, the material is suitable for the application of fruit peeling.